2018
DOI: 10.1093/intqhc/mzy103
|View full text |Cite
|
Sign up to set email alerts
|

Advancing the health of women and newborns: predictors of patient satisfaction among women attending antenatal and maternity care in rural Rwanda

Abstract: Patient-centeredness (including interpersonal relationships), organizational factors, and location are important individual determinants of satisfaction for women seeking maternal care at study facilities. Understanding variation in these factors should inform QI efforts in maternal and newborn health programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 25 publications
4
13
0
1
Order By: Relevance
“…Beyond clinical arguments for continuous support for women during childbirth [27, 64], the fact that having a companion improved mothers’ satisfaction, underlines the importance of allowing a person of choice to accompany them during birth. Consistent with findings from other studies [16, 43, 65], interpersonal relationships were important contributors to patient satisfaction. Mothers who had negative experiences during the process of care reported dissatisfaction more frequently than did those who had not had such experiences.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Beyond clinical arguments for continuous support for women during childbirth [27, 64], the fact that having a companion improved mothers’ satisfaction, underlines the importance of allowing a person of choice to accompany them during birth. Consistent with findings from other studies [16, 43, 65], interpersonal relationships were important contributors to patient satisfaction. Mothers who had negative experiences during the process of care reported dissatisfaction more frequently than did those who had not had such experiences.…”
Section: Discussionsupporting
confidence: 90%
“…High levels of satisfaction with care during childbirth have been reported in other low- and middle-income countries, such as in Ethiopia, Egypt, Malawi, Philippines, and Rwanda [3743], and in high-income countries, such as in Australia, England and Sweden [4446]. It has been questioned whether these high scores are an accurate representation of the mothers’ experiences [12].…”
Section: Discussionmentioning
confidence: 99%
“…Despite improved MNH quality of care and neonatal mortality, we found limited change in patient satisfaction. Mutaganzwa et al 19 described the baseline results in detail and found that patient-centeredness of care (including interpersonal relationships, respect, and privacy) and organizational factors such as cleanliness, comfort, and equipment/commodity availability were associated with higher satisfaction with care. Similar to other studies, one explanation for the lack of increased satisfaction corresponding with improved quality of care and outcomes could be that women were reluctant to share negative views or had low expectations of facility care and were satisfied with poor quality at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Informed consent was obtained from women surveyed for patient satisfaction. 19 This study was approved by the Institutional Review Board of Brigham and Women’s Hospital (2009-P-001941/11; BWH) and the Rwanda National Ethics Committee (RNEC 032/RNEC/2012).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a better understanding of patient satisfaction with rural medical services and potential determinants would help policy- and decision-makers to implement programs better tailored to rural patients’ health needs and desires and further improve rural health systems [30,31]. Some evidence has been found about patient satisfaction with rural medical services in Italy [25], South Africa [26], India [32,33], Rwanda [34], Bangladesh [35], Latin America [36], and the U.S. [37]. In China, one of the five key objectives of China’s new healthcare reform, launched in 2009, is to strengthen the basic-level health service delivery system, especially the rural health system.…”
Section: Introductionmentioning
confidence: 99%